Traits of intensive livestock systems in Algerian steppe territories. Issue 1 (31st December 2022) - Siad, Oussama; Deghnouche, Kahramen; Andrighetto, Igino; Contiero, Barbara; Marchesini, Giorgio; Bejaoui, Hanane; Chala, Adel; Cortese, Martina
Abstract: Weather hazards and changing climatic regimes combined with socio-cultural changes are forcing farmers living in Algerian steppe territories to find new strategies to maintain their business, particularly in terms of animal feeding sources. Animal's nutritional needs in the past used to be met mainly by grazing lands which nowadays cover less than 40% of feeding sources. This study aimed to determine the status of livestock system practices used by breeders in Algerian steppe territories and presents a novel method in identifying intensive systems. Data were obtained from 90 farms through a survey in the province of Tebessa. The farms were divided by their characteristics with a discriminant analysis by zone to know the characteristics of each region. Moreover, a discriminant analysis was performed to select the variables that best differentiated the farms characterised by a different percentage of feed purchased (PFP), which was taken as an index of intensive management. A stepwise regression analysis was also conducted to get predictors variables that mainly influence the percentage of feed purchased and characterise the intensive livestock farms in this area. As a result, livestock systems in steppe territories are up to changing to more intensive forms. These trends appear as solutions for farmers to improve their productivity in the face of various problems. Nevertheless, not to worsen the situation of livestock farming with the orientation towards the intensive system, it is important for farmers to be informed about international policies for practising intensive livestock farming. HIGHLIGHTS: The current state of livestock production and practices was identified in the steppe areas. The percentage of purchased feed had greater effects in determining the nature of the livestock systems and identifying intensive systems. The use of modelling techniques in the identification of livestock intensification could be successfully used in the differentiation of livestock systems.